Excess mortality associated with extreme heat in Rio de Janeiro, Brazil, 2023 - Rita Daniela Fernandez-Medina; Eduardo Mesquita Peixoto; Denis Rodrigues; Rodrigo Said; Cleonice Andrade Holanda; Cristina da Silva Freire; Aline Maria de Almeida; Silvia Cristina de Carvalho Cardoso; Mário Sergio Ribeiro; Claudia Maria Braga de Mello; Alexander Rosewell; Luciane Velasque (Revista Panamericana de Salud Pública)
Objective: To determine the excess mortality associated with the November 2023 extreme heat wave in Rio de Janeiro, Brazil, with temperatures reaching 42°C. Methods: Using the excess heat factor (EHF) to characterize the heat wave, this study identified elevated excess mortality across various disease categories, including symptoms and abnormal clinical findings, nervous system disorders, mental health conditions, and genitourinary diseases, diverging from typical heat-related mortality patterns. Results: This event resulted in an estimated excess mortality of 1 392 individuals in a short period, disproportionately affecting older adults and women, with a significant number of deaths occurring at home. The findings underscore the complexity of heat wave impacts and highlight gaps in health care access, risk perception, and clinical management. Conclusions: Heat waves are increasingly recognized as a significant public health threat, exacerbated by climate change, with profound impacts on morbidity and mortality. The study emphasizes the urgent need for comprehensive heat alert and response systems, intersectoral action plans, and public education to mitigate the effects of extreme heat. Furthermore, it calls for adaptive strategies in urban planning, housing, and public health policies to address the growing frequency and intensity of heat waves in the context of climate change. As Brazil faces escalating challenges from rising temperatures, particularly in urban centers, coordinated multisectoral efforts are essential to protect vulnerable populations and reduce heat-related mortality in the future.